Genitourinary syndrome of menopause treatment using lasers and temperature-controlled radiofrequency - Wańczyk-Baszak, Jadwiga; Woźniak, Sławomir; Milejski, Bartosz; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2018)
Perimenopausal changes caused by oestrogen deficiency are accompanied by a decrease in the content of collagen and elastin in the tissues, leading to thinning of the epithelium and the resultant disappearance of the superficial layer, which leads to smooth muscle dysfunction as well as connective tissue degradation. This aetiopathogenetic chain results in a set of symptoms experienced by approximately 50% of women in the peri- and postmenopausal period. Symptoms of dryness, burning, dyspareunia and urgency contribute to a significant reduction in the quality of sexual function and general comfort of life due to recurrent infections of the vagina, vulva and urinary tract. Different therapeutic methods may benefit genitourinary syndrome of menopause (GSM), while innovative methods such as lasers or radiofrequency deserve further study in this area.